Profusely carved Jangha (wall) of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
A closer view of the jangha (wall) of the temple is seen from its corner projection. All the projections and recesses that form the exterior of the garbhagriha (sanctum sanctorum) are profusely carved, containing various sculptures of ascetics, surasundaris (celestial damsels), and deities. The sculptures on the jangha are capped with chaitya dormer pediments.